THE VISUALLY IMPAIRED STUDENTS’ LEARNING ENGLISH APPLYING TOTAL PHYSICAL RESPONSE (TPR) - Wiyanah, Sri (ELTICS : Journal of English Language Teaching and English Linguistics, 2017)
The research aims to describe  the visually impaired students’ learning English using Total Physical Response (TPR). The research may contribute to the development of English learning model for the visually impaired students who need attention in their right to get better education and improvement in learning English using Total Physical Response (TPR). The research method was descriptive qualitative method. The study was conducted at Yaketunis Yogyakarta. There were fifteen visually impaired students who became participants in this research. The sources of the data were (1) visually impaired students as the participants of the study, (2) recorded actions (video-taped), (3) recorded interviews (audio-taped), and (4) field note. The result showed that visually impaired students had new experience in learning English effectively, actively, stress-free and joyful. Total Physical Responses handled that students’ limitation in visualization to get information through voice by their senses of hearing. The students practiced giving responses of some instructions, pronunced some words and repeated the words many times by maximizing their sense of hearing to activate their psychomotor competence. This process of learning activities supported them in developing their skill in mastering vocabulary, expression, and language command. Key words: Total Physical Response (TPR), Learning English, The visually impaired students